Technologies for Optimizing the System of Free Legal Aid in Ukraine, in line with the Recommendations of the Council of Europe - Petro VORONA; Mykola LAKHIZHA; Aleksandr BOKOV; Svitlana SYNENKO; Aleksandr CHERCHATY2 (Communications of International Proceedings, 2021)
The article analyzes the specifics, problems and prospects of optimizing the system and mechanisms of providing free legal aid in Ukraine on the basis of analysis of sources and literature and using the practical experience of the authors.  The authors emphasize the significant influence of international institutions on the development of necessary legislation and organizational support for the protection of citizens' rights in Ukraine.  It is noted that the SFLA in Ukraine is highly appreciated, which is confirmed by the expert opinions of the Council of Europe and the responses of citizens - clients of regional and local centers of free secondary legal aid.  Today, it is seen as an important element of an effective justice system based on such values as the rule of law and the protection of human rights. At the same time, a number of problems were observed in securing the rights of Ukrainians to legal aid.  Comparative analysis shows that most of these problems are characteristic of other post-communist countries, which is explained by the general patterns of post-communist transformation.  However, the national specificity of Ukraine, caused by periodic exacerbations of political confrontation, significant dynamics of legislation, difficult socio-economic situation, the presence of military conflict, etc., is also clearly visible.  The wide range of people who are eligible for secondary legal aid and the significant role of the SFLA in providing primary legal aid creates objective problems that can be considered temporary - growth problems - with due regard for them. In the authors' view, implementation of the Council of Europe's 2016 proposals, first and foremost to ensure the independence of the system, needs to be completed in order to enhance the impact of the SFLA work.  It is advisable to use the SFLA 's coordination capabilities in law enforcement work, which is particularly urgent in view of the significant reduction of the territorial units of the Ministry of Justice of Ukraine and the increasing role of local governments at the level of territorial communities.  Political stability, strengthening civil society and the completion of decentralization are important factors for positive change.  Ensuring the legal capacity of territorial communities should become a common task, and the role of SFLA in this area should grow.